(untitled) (Research, Society and Development, 2021)
This study aimed to evaluate the stress distribution in bone tissue, in Morse tapper implants and components supporting a single crown in the maxillary anterior area, under different bone anchorages (conventional, bicortical and bicortical with nasal floor elevation) and implant lengths (8.5 mm, 10 mm and 11.5 mm) using 3D finite element analyses. Three 3D models including element #11 were simulated using software InVesalius, Rhinoceros 3D and SolidWorks. Bone block models were reconstructed from computed tomography and simulated the placement of one implant of 4 mm of diameter and lengths above mentioned, supporting cemented zirconia crown. The 3D models were processed by the finite element FEMAP and NeiNastran software, using a load of 178N were applied at 0º, 30º and 60º, considering the implant long axis. Results were visualized as the von Mises stress, maximum principal stress and microstrain maps. Bicortical bone anchorages showed lower stress and microstrain bone tissue when compared to conventional bone anchorage. However, no differences were observed between bicortical and nasal floor elevation. Regarding implants and components, the stress distribution was similar between models with little stress relief in the apical region of the implants for implants with conventional anchorage. The conclusion drawn from this study is that non-axial loading showed worse biomechanical behavior for bone tissue and implants/components. The bicortical techniques (bicortical and nasal floor elevation) should be preferred during the implant placement to reduce the stress and microstrain in the bone tissue.